Analisis Pengaruh Ukuran Training of Trainer (ToT) PL-KUMKM Provinsi Kalimantan Utara Tahun 2022 - Risna Yuliani (Trunojoyo University of Madura, 2022)
One of indicators of the success of the Thematic Sectoral Statistical Assistance (PSST) PL-KUMKM Statistical Office Kalimantan Utara−Department of Industry, Trade, Cooperatives and SMEs (Disperindagkop UKM) is the implementation of the Training of Trainer (ToT) Data Collection Officers in 2022. This study aims to analyze how big the success rate and how prominent is the effect size in the ToT of PL-KUMKM officers in North Kalimantan Province. This research includes explanatory research with quantitative methods. Data was collected using google forms for all participants. The data analysis technique used is descriptive analysis and inferential analysis. The data was processed using the RStudio application or R program. The results showed that the ToT PL-KUMKM went marvelously because of compelling differences in the Pre-Test and Post-Test scores. The coefficient Cohen's d effect size reveals the number is 2,013 and the average distance is 17,625 with µ=0 which means the effect is very influential (massive).